106 Implantable cardioverter-defibrillators in the elderly: a single-centre observational study on outcomes in octogenarians. (4th June 2021) - Ng, Shermayne; Kay, Jamie; Makharia, Manoj; Wick, Caroline; Khiani, Raj
Abstract : Introduction: Implantable cardioverter-defibrillators (ICDs) are well-established therapy for sudden cardiac death (SCD) prevention. However, the average age of patients in both primary and secondary prevention clinical trials of ICDs has been in the 60s, with less than 25% of included participants above the age of 75. As such, data supporting the clinical and cost-effectiveness of ICDs in this understudied age group is lacking. We aim to review the outcome of patients > 80 years of age with ICD therapy in a district general hospital serving an elderly population. Methods: Patients > 80 years of age who underwent ICD implantation between 2015 and 2017 were identified from the hospital electronic records. Conventional ICD and cardiac resynchronisation therapy with defibrillator (CRT-D) implants were included. Primary outcomes include overall all-cause mortality at time of data collection and at 1-year following implant. Secondary outcomes include number of patients receiving appropriate and inappropriate therapy and complication rates. Results: We identified 38 patients >80 years of age who underwent a defibrillator implantation in this period. 17 and 21 patients received an ICD and CRT-D respectively. 29 (76%) were male and the mean age at implant is 83.3 years. The mean follow-up period was 37.3 months (range: 6 – 51 months). The average number of co-morbidities per patient was 4. The most common comorbidities were heart failure with reduced ejection fraction (32/38), ischaemic heart disease (27/38), hypertension (22/38) and atrial fibrillation (21/38). 11 of 38 patients had chronic kidney disease. 25 patients (66%) underwent ICD implantation as primary prevention therapy. The overall mortality rate was 26.3% and the 1-year mortality rate was 2.6%. The average time to death from implant was 2.2 years. 6 patients (16%) received appropriate shocks during the follow-up period. No patients received inappropriate shocks. There were no acute or late complications from device implantation in the follow-up period. Conclusion: In this single-centre observational study, ICD implantation in octogenarians had a low complication rate. The majority of patients survived beyond 12 months, although the average time from implant to death was just over 2 years. ICD therapy may be beneficial in octogenarians and patients should be considered for ICD therapy after careful selection and counselling of risks and benefits. Further work is required to identify patients in this age group whom may benefit the most from ICD therapy. Conflict of Interest: None